ANALISIS RANTAI MARKOV UNTUK MENGETAHUI PERPINDAHAN MEREK SEPEDA MOTOR PADA MAHASISWA TEKNIK INDUSTRI UNIVERSITAS UDAYANA - I Putu Ivananda Indra Artadana (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to analyze the probability of Unud Industrial Engineering Students switching from one brand of motorbike to another. The Markov Chain method is used in this research to analyze the probability of the move. This analysis was carried out to identify transitions between motorbike brands used by students, with a focus on Marketing Variables that influence brand switching decisions. The survey was conducted on Industrial Engineering Students at Udayana University. The motorbike brands analyzed are Yamaha, Honda, Kawasaki, Suzuki and Piagio. From the calculation of each market share until it is in a stable condition, the results obtained are Honda at 52.6%, Yamaha at 33.1%, Kawasaki at 2.1%, Suzuki at 0.1%, and Piaggio at 9.4% The results of the analysis are expected to provide in-depth insight into the dynamics of motorbike brand switching among Industrial Engineering students at Udayana University, which can be a basis for decision making in the motorbike and marketing industry. This research is expected to contribute to the understanding of consumer behavior in the context of brand switching, especially in the Industrial Engineering student population.